Ni-doped Co-layered Double Hydroxides as High-performance Electrocatalyst for the Hydrogen Evolution Reaction - Chaudhari, Ashim; Kandel , Mani Ram; Ali, Abid; Paudel, Dasu Ram; Dahal , Bipeen; Subedi, Subhangi (Journal of Nepal Chemical Society, 2025)
The development of cost-effective and efficient electrocatalysts for the hydrogen evolution reaction (HER) is crucial for advancing sustainable hydrogen production. In this study, nickel-doped cobalt-layered double hydroxides (Ni-Co-LDH) were successfully synthesized using a simple room-temperature aging method. This one-step process allows for the uniform incorporation of nickel into the cobalt LDH structure, which significantly improves catalytic activity. The synthesized Ni-Co-LDH catalysts demonstrated excellent HER performance in alkaline conditions, with low overpotentials of 104 mV at 10 mA cm⁻² and 204 mV at 50 mA cm⁻². The enhanced performance is attributed to the synergistic effect between nickel doping and the cobalt-LDH, which creates an optimized surface for hydrogen evolution and accelerates charge transfer. Scanning electron microscopy (SEM) confirmed a uniform and favorable surface morphology, while electrochemical impedance spectroscopy (EIS) showed improved charge transport kinetics. These results suggest that Ni-Co-LDH is a highly promising, low-cost material for high-performance electrocatalysis in HER. The ease of synthesis, combined with its high efficiency, makes this catalyst a strong candidate for large-scale hydrogen production, contributing to the development of renewable energy solutions.